Retro-priming, priming, and double testing: psi and replication in a test–retest design - Rabeyron, Thomas (Frontiers in Human Neuroscience, 2014)
Numerous experiments have been conducted in recent years on anomalous retroactive influences on cognition and affect (Bem, 2010), yet more data are needed to understand these processes precisely. For this purpose, we carried out an initial retro-priming study in which the response times of 162 participants were measured (Rabeyron & Watt, 2010). In the current paper, we present the results of a second study in which we selected those participants who demonstrated the strongest retro-priming effect during the first study, in order to see if we could replicate this effect and therefore select high scoring participants. An additional objective was to try to find correlations between psychological characteristics (anomalous experiences, mental health, mental boundaries, trauma, negative life events) and retro-priming results for the high scoring participants. The retro-priming effect was also compared with performance on a classical priming task. Twenty-eight participants returned to the laboratory for this new study. The results, for the whole group, on the retro-priming task, were negative and non-significant (es = -.25, ns) and the results were significant on the priming task (es = .63, p < 001). We obtained overall negative effects on retro-priming results for all the sub-groups (students, male, female). Ten participants were found to have positive results on the two retro-priming studies, but no specific psychological variables were found for these participants compared to the others. Several hypotheses are considered in explaining these results, and the author provide some final thoughts concerning psi and replicability.